Differences in Serum Lipid Profile Value in Pregnancy and Postpartum on Severe Preeclampsia - White, I Putu F I; Wantania, John J E; Mewengkang, Maya E (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract                     Objective:Uncovering the connection of serum lipid profile (total cholesterol, triglyceride, HDL, LDL, VLDL) with preeclampsia in pregnancy and postpartum, and its outcome. Method:This is a cross-sectional comparative analytic study Result:From 28 preeclampsia subject were found, mean value of systole 165.36 mmHg and 105.71 diastole. Serum lipid profile in pregnancy and postpartum has a significant differences and correlated with preeclampsia, total cholesterol 234.5 mg/dl and 192.71 mg/dl, p=0.000; medium positive in pregnancy with systole r=0.461; p=0.013, weak positive with diastole r=0.380; p=0.046; postpartum with systole medium positive r=0.615; p=0.001, and weak positive with diastole r=0.317; p=0.100. LDL 140.5 mg/dl and 102.5 mg/dl, p=0.000; pregnancy and systole r=0.446; p=0,017; and postpartum were medium positive r=0.546; p=0.003. HDL 51.5 mg/dl and 43.5 mg/dl, p=0.003; not correlated with BP. Triglyceride 268.89 mg/dl and 208.96 mg/dl, p=0.000; pregnancy r=0.516; p=0.005; postpartum r= 0.515; p=0.005 has medium correlation with systole. VLDL 53.78 mg/dl and 41.79, p=0.000; pregnancy r=0.461; p=0.013 systole medium positive; r=0.380; p=0.046 diastole weak positive; postpartum r=0,615; p=0,001 systole strong positive. Conclusion:All parameter of serum lipid profile in pregnancy and postpartum has significant differences and related with severe preeclampsia. Total cholesterol, LDL, triglyceride, and VLDL correlated with BP in severe preeclampsia. Key word:endothelial dysfunction, lipid profile, preeclampsia.   Abstrak Tujuan: Untuk mengetahui hubungan profil lipid serum (kolesterol total, trigliserida, HDL, LDL, VLDL) dengan preeklampsia dan luarannya dalam kehamilan dan postpartum. Metode: Penelitian ini merupakan studi potong lintang analitik komparatif Hasil: Dari 28 subjek dengan preeklamsia, ditemukan rerata systole 165,36 mmHg dan 105,71 diastole. Profil lipid serum dalam kehamilan dan postpartum ditemukan berbeda bermakna dan berhubungan dengan preeklampsia berat, kolesterol total 234,5 mg/dl dan 192,71 mg/dl, p=0,000; kehamilan dengan sistole positif sedang  r=0,461; p=0,013, diastole positif lemah r=0,380; p=0,046; postpartum dengan sistole positif sedang r=0,615; p=0,001,  dan diastole postitif lemah r=0,317; p=0,100. LDL 140,5 mg/dl dan 102,5 mg/dl, p=0,000; dalam kehamilan dengan sistole r=0,446; p=0,017;  dan postpartum positif sedang r=0,546; p=0,003. HDL 51,5 mg/dl dan 43,5 mg/dl, p=0,003; tidak berkorelasi dengan TD. Trigliserida 268,89 mg/dl dan 208,96 mg/dl, p=0,000; kehamilan r=0,516; p=0,005; postpartum  r= 0,515; p = 0,005 korelasi positif sedang dengan sistole.  VLDL 53,78 mg/dl dan  41,79, p=0,000; kehamilan r=0,461; p=0,013 positif sedang dengan sistole; r=0,380; p=0,046 positif lemah dengan diastole; postpartum r=0,615; p=0,001 positif kuat dengan sistole. Kesimpulan: Seluruh parameter profil lipid serum kehamilan dan postpartum ditemukan memiliki perbedaan bermakna dan berhubungan dengan preeklampsia berat. Kolesterol total, LDL, trigliserida, dan VLDL ditemukan berhubungan dengan TD pada PEB. Kata kunci: disfungsi endothel, lipid, preeklampsia.